Diskursus Fikih Indonesia: Dari Living Laws Menjadi Positive Laws - M. Noor Harisudin (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2016)
This paper discusses how the Indonesian fiqh (Islamic jurisprudence) is formulated. The Indonesian fiqh idea that was first conceptualized academically by T.M. Hasbi As-Shiddieqy moved from the so-called living laws into positive laws. Indonesian fiqh discourse born in Indonesia is a form of fiqh (Islamic jurisprudence) that solves the problem of the reality of Indonesian people in line with the growth and development of the country that has the largest Muslim population in the world. Not surprisingly, in the context of Indonesian fiqh, there are born many contemporary fiqh variations in more specific domains, such as environmental fiqh, social fiqh, figh of pluralism, fiqh of women, and many others. In three periods, which are the period of beginning (pioneering), the period of development, and the period of legislating (taqnin), Indonesian fiqh that is based on contemporary issues and considered as living laws is further proposed to become positive laws that are binding to the entire Muslim community in Indonesia.